Pengolahan Air Bersih dengan Metode Filtrasi Sederhana untuk Kebutuhan Air Layak Konsumsi di Pulo Kampai - Said , Aja Avriana; Lilis, Lilis; Rispianti, Dina (IRA Jurnal Pengabdian Kepada Masyarakat (IRAJPKM), 2025)
The issue of clean water availability remains a challenge in several rural areas, including Pulo Kampai village, Pangkalan Susu Subdistrict, Langkat Regency, North Sumatra. This community service activity aims to improve community understanding and skills in treating clean water using a simple filtration method. The methods used include education, training on filtration tool making, and testing the filtration results using local water sources. The results show that the filtration method using gravel, sand, activated charcoal, and cotton effectively improves water quality visually and sensorially. This activity has provided tangible benefits in supporting the availability of potable water for the local community.